Adaptasi Nelayan Kawasan Perbatasan Di Desa Sei Pancang Kecamatan Sebatik Utara Kabupaten Nunukan Provinsi Kalimantan Timur - Poppy Setiawati Nurisnaeny (Jurnal Communicate, 2016)
Indonesia boundaries have abundant potentials of natural resources, but the lack of human capital and human empowerment might caused complex problems, such as the existence of the traditional fishermen in the border areas. The fishermen are identical as the asset limitation, lack of capital, lack of bargaining position and also limited to the market access. The fishermen are mostly depending on the environment and natural condition, thus the “unfair” situations, reflected to their difficulties to all eviate poverty. The focus of the research is to observe the adaptation of the traditional fishermen in the border area, which is Sei Pancang village. The research shows that the adaptation of Sei Pancang fishermen in overcoming their difficulties of life in the border area is done by applying cultural value, utilizing available resources, and maintaining social and economic cross-country relationships in the form of patron-client relationship with the Toke of Tawau. The border area between Sei Pancang village and Tawau town is characterized by interdependent borderland of these region in fulfilling their resources. The findings also indicate that this border area have a role in the adaptation of the fishermen in the border area.